DETERMINAN STATUS GIZI ANAK USIA SEKOLAH DASAR - Yulita Yulita; Herti Juliani Gulo; Tuty Hertati Purba; Wanda Lestari; Agnes Sry Vera Nababan (JOURNAL HEALTH AND NUTRITIONS, 2022)
The current nutritional condition shows two extreme conditions, namely malnutrition and excess nutrition. Based on the initial survey conducted at SDN 071079 Mandrehe District, out of 10 students whose nutritional status was seen, 7 students were classified as overweight and 3 students had good nutritional status. The impact of nutritional problems is more visible with the increase in degenerative diseases, such as coronary heart disease, diabetes mellitus, hypertension and liver disease. To prevent this impact, efforts are needed to improve children's diet so that the type and amount of food intake is in accordance with needs. Objective Knowing the relationship between nutritional intake, breakfast and consumption of fast food with the nutritional status of school-age children at SDN 071079 Mandrehe District, West Nias Regency. Methods This type of research is analytic observational with a cross sectional study design. The sampling method in this study was using random sampling with a sample of 60 samples. Collecting data using questionnaires and interviews. The test used is the Spearman rank test. Results Research shows that the variables of nutritional intake, breakfast and consumption of fast food have a significant relationship with the variable nutritional status with a value of p = (<0.05). Conclusion  There is a relationship between nutritional intake, breakfast and fast food consumption with the nutritional status of school-age children at SDN 071079, Mandrehe District, West Nias Regency.Kondisi zat gizi saat ini menunjukkan dua hal kondisi yang ekstrem, yaitu kekurangan gizi dan kelebihan gizi. Berdasarkan survei awal yang dilakukan di SDN 071079 Kecamatan Mandrehe, dari 10 siswa yang dilihat status gizinya terdapat 7 siswa tergolong status gizi lebih dan 3 siswa status gizi baik. Dampak masalah gizi lebih tampak dengan semakin meningkatnya penyakit degeneratif, seperti jantung coroner, diabetes mellitus, hipertensi dan penyakit hati. Untuk mencegah dampak ini perlu usaha dalam memperbaiki pola makan anak agar jenis dan jumlah asupan makan sesuai dengan kebutuhan. Tujuan Mengetahui hubungan antara asupan gizi, sarapan pagi dan konsumsi fast food dengan status gizi anak usia sekolah di SDN 071079 Kecamatan Mandrehe Kabupaten Nias Barat. Metode Jenis penelitian yaitu observasional analitik dengan rancangan cross sectional study. Metode pengambilan sampel dalam penelitian ini yaitu menggunakan random sampling dengan sampel penelitian sebanyak 60 sampel. Pengambilan data menggunakan kuesioner dan wawancara. Uji yang digunakan yaitu uji rank spearman. Hasil Penelitian menunjukkan variabel asupan gizi, sarapan pagi dan konsumsi fast food memiliki hubungan signifikan dengan variabel status gizi dengan nilai p = (<0,05). Kesimpulan Ada hubungan asupan gizi, sarapan pagi dan konsumsi fast food dengan status gizi anak usia sekolah di SDN 071079 Kecamatan Mandrehe Kabupaten Nias Barat.